Cochrane Database of Systematic Reviews 2002
DOI: 10.1002/14651858.cd003831
|View full text |Cite|
|
Sign up to set email alerts
|

Celecoxib for rheumatoid arthritis

Abstract: For an individual with RA the potential benefits of celecoxib need to be balanced against the uncertainty that the short-term reduced incidence of upper GI complications are maintained in the long-term and its increased cost in comparison to traditional NSAIDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“…Recently, joints from RA patients exhibited abundant COX expression, to higher levels than those found in synovial tissues from osteoarthritis patients or nonarthritic synovial tissues [24]. Therefore, COX-2-targeted therapy is under consideration for the treatment of RA by inhibiting inflammation and angiogenesis [25][26][27]. In the present study, it was shown that MDR also inhibited COX-2 mRNA expression in a concentration-dependent fashion.…”
Section: Discussionmentioning
confidence: 52%
“…Recently, joints from RA patients exhibited abundant COX expression, to higher levels than those found in synovial tissues from osteoarthritis patients or nonarthritic synovial tissues [24]. Therefore, COX-2-targeted therapy is under consideration for the treatment of RA by inhibiting inflammation and angiogenesis [25][26][27]. In the present study, it was shown that MDR also inhibited COX-2 mRNA expression in a concentration-dependent fashion.…”
Section: Discussionmentioning
confidence: 52%
“…53,[112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130] Two foreign language systematic reviews were not included due to difficulties in obtaining the references within the project time frame. 131,132 Three aspects of these reviews were assessed in detail:…”
Section: Current Use Of Nsaidsmentioning
confidence: 99%
“…However, NSAIDs including COX-2 inhibitors for pain relief in OA is accompanied by increased risk of adverse effects in long-term treatment such as gastrointestinal problems and cardiovascular risks [13]. Furthermore, no evidence of any clinically significant drug interactions for glucosamine or chondroitin was reported as well.…”
Section: Safety Profile Of Glucosamine and Chondroitinmentioning
confidence: 99%
“…However, some studies have indicated that NSAIDs are only used to treat symptoms without correction of the degenerative disorder of the connective tissue. Furthermore, the long-term use of NSAIDs causes potential adverse effects on the gastrointestinal and cardiovascular systems, which are mainly popular among elderly patients [13]. Therefore it can be deduced that medical treatments available for OA are moderately effective and are mostly directed at short-term pain relief, In addition, side effects of these treatments can be quite significant.…”
Section: Introductionmentioning
confidence: 99%